2018
DOI: 10.3354/aei00288
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effects of bivalve mariculture on water quality in northern New Zealand using 15 years of MODIS-Aqua satellite observations

Abstract: This study demonstrates that satellite information can be used to quantify the effect of a large coastal mussel farm on water quality. Our study focussed on a 1400 ha area of maricultured green-lipped mussels Perna canaliculus in the Firth of Thames in northern New Zealand. Observations by NASA's MODIS-Aqua sensor were used to estimate the concentration of chlorophyll a (chl a, as a proxy for phytoplankton), turbidity and sea surface temperature at 500 m resolution. We used approximately 890 single-pass satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Furthermore, the underway pCO 2 surveys surrounding the large suspended mussel farms in the eastern Firth (Figure 2C) showed no clear signal of pCO 2 modification in proximity to the farms, with respect to overall variability of pCO 2 over the larger Firth/Hauraki Gulf area. This was consistent with the remote sensing studies of Pinkerton et al (2018) that showed negligible water quality (chl-a and turbidity) effects of those farms, arising as a consequence of their very high water flushing rates. Water-column average variations of DIC concentration were consistent with variations of column-average net DIC flux calculated by the mass-balance analysis of Zeldis and Swaney (2018), made using nutrient, salinity and hydrometric data collected during the present study.…”
Section: Attributing Factors Controlling Carbonate and Oxygen Variationsupporting
confidence: 91%
“…Furthermore, the underway pCO 2 surveys surrounding the large suspended mussel farms in the eastern Firth (Figure 2C) showed no clear signal of pCO 2 modification in proximity to the farms, with respect to overall variability of pCO 2 over the larger Firth/Hauraki Gulf area. This was consistent with the remote sensing studies of Pinkerton et al (2018) that showed negligible water quality (chl-a and turbidity) effects of those farms, arising as a consequence of their very high water flushing rates. Water-column average variations of DIC concentration were consistent with variations of column-average net DIC flux calculated by the mass-balance analysis of Zeldis and Swaney (2018), made using nutrient, salinity and hydrometric data collected during the present study.…”
Section: Attributing Factors Controlling Carbonate and Oxygen Variationsupporting
confidence: 91%
“…riverine influence along the southern New Zealand coast and large-scale land-use changes (Schiel and Howard-Williams, 2016;Stevens et al, 2021) and the coastal focus of this study. While the chl-a concentration (Pinkerton et al, 2018) and water clarity algorithms used in this study have been developed to better account for the often turbid waters of southern New Zealand, these case-2 coastal waters present challenges for determining metrics of both light availability (K d ) and phytoplankton biomass. However, the utility of remote sensing to retrospectively assess the effects of multiple physical and biotic parameters on kelp beds has great utility to better understand the interaction between local and global scale stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used an average of values found for oceanic phytoplankton (Bricaud et al, 1995;Bissett et al, 1997), and measurements in the lower reaches of New Zealand rivers and estuaries. We blended the QAA-chl-a and the MODIS-default chl-a product (NASA, 2018) using a logistic-scaling of bbp(555) (Pinkerton et al, 2018).…”
Section: Chlorophyll-amentioning
confidence: 99%
See 2 more Smart Citations